2007
DOI: 10.1203/01.pdr.0000249981.70618.18
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor Ligands and CD154 Stimulate Microglia to Produce a Factor(s) That Promotes Excess Cholinergic Differentiation in the Developing Rat Basal Forebrain: Implications for Neurodevelopmental Disorders

Abstract: Maternal inflammation plays a role in the etiology of certain neurodevelopmental disorders including autism and schizophrenia. Because maternal inflammation can lead to activation of fetal microglia, we have examined effects of inflamed microglia on cultured neural progenitors from rat embryonic septal region and basal forebrain. These cells give rise to cholinergic neurons projecting to cortex and hippocampus. Microglia stimulated with lipopolysaccharide (LPS), peptidoglycan, Poly I:C and CD154 produce condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Culture studies have demonstrated that factors produced by activated microglia promote cholinergic differentiation of undifferentiated embryonic BF precursor cells (18)(19)(20). Whether MIA results in increased ChAT activity or increased numbers of cholinergic neurons in the fetal BF in vivo has not been investigated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Culture studies have demonstrated that factors produced by activated microglia promote cholinergic differentiation of undifferentiated embryonic BF precursor cells (18)(19)(20). Whether MIA results in increased ChAT activity or increased numbers of cholinergic neurons in the fetal BF in vivo has not been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from our laboratory and those of others have shown that a cocktail of factors released from stimulated microglia induces cholinergic differentiation of undifferentiated precursors from the mid-gestational basal forebrain (BF) (18)(19)(20). Moreover, activity of choline acetyltransferase (ChAT), the hallmark of cholinergic neurons, is elevated in the BFs of autistic subjects (21), and post-mortem analysis reveals an increased number and an enlargement of cholinergic BF neurons in autistic children (22).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…18 In the CNS, TLR activation was shown to promote cholinergic differentiation from neural progenitors in the developing rat basal forebrain. 19 TLRs on neural progenitor cells (NPCs) were recently demonstrated to be directly involved in regulating adult hippocampal neurogenesis. 20 These observations have extended the function of TLRs in mammals from the realm of immunity to cellular development more generally.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%